An Analysis of the Accuracy of Manufacturing Overhead Cost Allocation in Establishing Competitive Selling Prices: A Case Study of UD. Cipta Mandiri - Nur Fauziah Purba; Aqwa Naser Daulay; Hendra Hermain (JURNAL ECONOMINA, 2026)
This study aims to analyze the accuracy of factory overhead cost allocation in determining competitive selling prices at UD. Cipta Mandiri. The research employed a qualitative approach using a case study method, with data collected through interviews, observations, and documentation. The analysis was conducted by calculating the cost of production using the full costing method and determining the selling price through the cost-plus pricing approach. The results indicate that factory overhead costs have not been allocated accurately, resulting in selling prices that are not competitive. Based on the full costing method, a price difference ranging from 22% to 27.8% was identified compared to the traditional costing method, indicating a tendency toward overcosting. The application of the full costing method provides a more accurate calculation of production costs and enables the company to establish more rational and competitive selling prices. Therefore, the accuracy of factory overhead cost allocation plays an important role in enhancing business competitiveness